ANALYSIS OF MARKET INTEGRATION OF NIGERIAN TOMATO MARKETS - Angela Ebere OBETTA; Anthonia Ifeyinwa ACHIKE; Nnameka Andegbe CHUKWUONE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Poor market integration affects market liberalization and handling of shocks such as covid-19. This study, therefore, investigates the market integration of tomato and its determinants in Nigeria. Johansen co-integration techniques, autoregressive distributed lag, the error correction model, bootstrapping regression and granger causality test were used to achieve the objectives of the study. The results revealed that most tomato markets in Nigeria were not integrated. This shows that tomato prices in most markets in different regions of Nigeria were not well integrated which could affect the transmission of price. From the Granger causality test results, ten tomato producing states Granger caused the demanding states, while only two demanding states granger caused the producing states. The adjustment term (-0.849924) shows that the reversion to long-run equilibrium is at an adjustment speed of 84.9924%. Distance, population and self-sufficiency had a negative influence on tomato market integration while the telephone had a positive influence on tomato market integration. Thus, the distance between two markets, population and self-sufficiency inhibits the flow and transmission of price information among tomato markets across the country which, in turn, lower market integration. The presence of telephone in Nigerian markets enhanced the flow of price information from one market to others and consequently increase market integration. These findings call for upgrading and investing in infrastructure, such as roads, and regulating information and telephone services by the government.